Development and quality evaluation of spent hen meat spread incorporated with corn starch - Ranade, Ashlesha; Malav, Om Prakash; Mehta, Nitin; Wagh, Rajesh V.; Sharma, Rajnish (Journal of Meat Science, 2023)
Three different levels of corn starch i.e. 4%, 6% and 8% was incorporated after replacing meat in the formulation of spent hen meat spread (SHMS). The lowest scores for most of the sensory parameters were observed in product with 4% level of corn starch whereas the product with 6% corn starch level had highest scores for all the sensory parameters. Lightness values of SHMS increased significantly (P<0.05) with increase in level of corn starch level, whereas the redness (a*) and yellowness (b*) values decreased significantly (P<0.05) with the addition of corn starch. The pH of the treated spent hen meat spread showed significantly (P<0.05) declining trend on incorporation of corn starch. Cooking yield and moisture content showed increasing trend with the increase in the incorporation level of corn starch. Protein and fat values were recorded lower in treatment products in comparison to control product. On basis of analysis of sensory parameters, instrumental colour profile, physico-chemical properties and proximate composition, the incorporation of corn starch at 6% level was found best for the preparation of excellent quality spent hen meat spread.